THE KITE FLAP IN THE TREATMENT OF FINGER TIP AMPUTATIONS Case Report - Munir, Muh. Ardi (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2015)
Background. Fingertip injuries are extremely common. Out of the various available reconstructive options, one needs to select an option which achieves a painless fingertip with durable and sensate skin cover. The present analysis was conducted to evaluate the management and outcome of fingertip injuries. In contrast to amputations of a single finger, bone shortening and wound closure usually should not be considered for thumb soft tissue defects. In general, the thumb should never be shortened. The flap has a consistent arterial supply, good sized veins, and terminal branches of the superficial radial nerve.Case report. Male 42 years old with traumatic amputation at the right thumb. Suffered since 5 days before admitted to the hospital due to livestock string roll attraction that happens suddenly. There is thumb tip loss at the level of IP joint, bony expose, swelling, skin and soft tissue defect at the level of mid shaft of the proximal phalanx. Radiographic study shown that there is loss of distal phalanx of thumb.Procedure. The kite flap for thumb tip defect or amputation. Flap is raised from the dorsum of the first phalanx of the index finger, including the metacarpophalangeal (MTP) joint.Conclusion. The treatment needs to be individualized and all possible techniques of reconstruction must be known to achieve optimal recovery. The results showed preservation of finger length and contour, retention of sensation and healing without significant complication. Thumb tip defects should be aggressively treated to preserve thumb length, which is more important to the thumb's overall contribution to hand function than joint flexibility, in contradistinction to the fingers. Accordingly, the rectangular volar advancement is the preferred option for small thumb tip defects as it brings sensate durable skin to the thumb tip. Larger full-thickness defects of the thumb require sensate resurfacing with either the dorsum of the first phalanx of the index finger or kite flap.Keywords: Fingertip injury, thumb tip defect/amputation, kite flap.